Property Rights Versus Public Spirit: Ownership and Efficiency of U.S. Electric Utilities Prior to Rate-of-Return Regulation - Hausman, William J.; Neufeld, John L. (The Review of Economics and Statistics, 1991)
William J. Hausman, John L. Neufeld, Property Rights Versus Public Spirit: Ownership and Efficiency of U.S. Electric Utilities Prior to Rate-of-Return Regulation, The Review of Economics and Statistics, Vol. 73, No. 3 (Aug., 1991), pp. 414-423